2019
DOI: 10.3138/cjhs.2019-0024
|View full text |Cite
|
Sign up to set email alerts
|

More than one flavour: University students’ specific sexual fantasies, interests, and experiences

Abstract: Sexual fantasies, interests, and experiences are three important aspects of human sexual expression that likely are related yet distinct. Updated and comprehensive information on patterns in these three areas of sexual expression is important for developing knowledge on the extent to which fantasies are distinct from interests and experiences as well as whether social sexual norms are changing. Thus, the overall goal of this study was to explore patterns in university students’ sexual expression. Participants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 49 publications
1
23
0
Order By: Relevance
“…Similar levels of paraphilic fantasies have been found in other community studies (e.g. Joyal 2015;Noorishad et al 2019). A further Canadian study by Joyal and Carpentier (2017) of 1040 men and women from a representative community sample found that approximately half of the sample indicated an interest in at least one paraphilia and approximately one-third had engaged in paraphilic-related behaviour at least once.…”
supporting
confidence: 80%
“…Similar levels of paraphilic fantasies have been found in other community studies (e.g. Joyal 2015;Noorishad et al 2019). A further Canadian study by Joyal and Carpentier (2017) of 1040 men and women from a representative community sample found that approximately half of the sample indicated an interest in at least one paraphilia and approximately one-third had engaged in paraphilic-related behaviour at least once.…”
supporting
confidence: 80%
“…However, the prevalence of paraphilic (and bondage/discipline, dominance/submission, sadism/ masochism; BDSM) interests in the general population is usually higher than that of corresponding behaviors (Ahlers et al, 2011;Holvoet et al, 2017;Joyal & Carpentier, 2017). The few studies that directly assessed concordance between paraphilic interests and behaviors in the general population found positive significant associations, as expected, although with fluctuating magnitudes (ranging from medium to relatively large correlations, usually between .30 and .65; Bártová et al, 2021;Dombert et al, 2016;Knack, 1982;Noorishad et al, 2019;Person et al, 1992;Seto et al, 2021;Williams et al, 2009). One issue with associations between paraphilic interests and behaviors is that most scales include "no interest" and "no behavior" as response choices (e.g., Bártová et al, 2021).…”
Section: Introductionmentioning
confidence: 82%
“…Research indicates that fantasizing about a deviant sexual act is often linked with en gagement in the act itself by both non-offending members of the community (Klein, Schmidt, Turner, & Briken, 2015) as well as individuals previously convicted of a sexual offense (Turner-Moore & Waterman, 2017). However, recent studies have found that this relationship is not straightforward, with fantasy-behavior correlations observed in community samples being weaker for deviant content than for non-deviant content (Noorishad et al, 2019). Also, in a sample of only minor-attracted men, sexual fantasizing about children was not correlated with sexual offending behavior (Bailey, Bernhard, & Hsu, 2016).…”
Section: The Link Between Sexual Fantasizing and Sexual Offendingmentioning
confidence: 90%
“…When sexual mental imagery concerns an act that is deemed culturally unacceptable (e.g., pedophilia, voyeurism, frottage, exhibitionism, fetishism, biastophilia, or sadism), it is said to be "deviant". The use of a deviant sexual fantasy is typically aligned with an existing deviant sexual interest (Noorishad, Levaque, Byers, & Shaughnessy, 2019) and deviant sexual fantasizing has been found to be an etiological factor for sexual offending (Seto, 2019) as well as a key risk factor for sexual recidivism (Mann, Hanson, & Thornton, 2010). However, not all deviant sexual fantasies are "high risk", and not all "high risk" fantasies lead to sexual offenses.…”
Section: Sexual Fantasy Vs Sexual Fantasizingmentioning
confidence: 99%